The attitudes of political parties in Turkey towards the EU after the 2002 elections - Alagöz, Helin (My University, 2012)
Seçmen tercihlerini temsil eden tek meşru birim olarak siyasi partiler demokrasilerin vazgeçilmez parçalarıdır. Onların AB konusundaki duruşları ülkelerinin AB ile olan ilişkilerinin şekillenmesinde önemli rol oynar. Bu tezin odak noktası Türk siyasi partilerinin 2002 genel seçimlerinden sonra Avrupa Birliği’ne karşı tutumlarıdır. Bu bağlamda, Adalet ve Kalkınma Partisi, Cumhuriyet Halk Partisi, Milliyetçi Hareket Partisi ve Barış ve Demokrasi Partisi olmak üzere dört büyük parti ele alınarak 2002-2011 Adalet ve Kalkınma Partisi hükümetleri döneminde bu partilerin AB yaklaşımları analiz edilmektedir. İncelenen partilerin AB yaklaşımlarının tutarlı olup olmadığı ve eğer tutarlı değilse AB duruşlarının neden değiştiği sorulmaktadır. Tezde rasyonel seçim teorisi yardımcı kalitatif araştırma yöntemleri ile birlikte Türk siyasi partilerinin AB politikalarını analiz etmek için kullanılmıştır. Buna göre, Türkiye’deki siyasi partilerin AB yaklaşımlarının belli dönemlerde farklılaştığı tespit edilmiştir. Bir defa bu partilerin tutarlı bir AB politikası izlemedikleri çıkarımı yapıldıktan sonra, partilerin AB duruşlarındaki değişiklikler onların maliyet-fayda analizleriyle açıklanmıştır. Partilerin AB politikaları üzerine yapılan araştırmanın tüm bulgularının ışığında seçmen davranışı, parti içi dinamikler ve parti kimliğinin partilerin çıkar algılamalarını etkileyen en önemli değişkenler olduğu sonucuna varılmıştır. Başka bir deyişle, bu değişkenler partilerin AB duruşlarını belirleyen temel faktörler olmuştur.

As the only legitimate units representing voter preferences, political parties are the indispensable elements of electoral democracies. Their stances concerning the EU issue play an important role in shaping their country’s relations with the EU. The focus of this thesis is the attitudes of Turkish political parties towards the European Union after the 2002 general elections in Turkey. In this context, it takes four major political parties into account, namely the Justice and Development Party, the Republican People’s Party, the Nationalist Action Party and the Peace and Democracy Party and analyzes their EU approaches between 2002 and 2011 during the Justice and Development Party governments. It asks whether those parties have consistent EU approaches; and if not, why they change their EU stances. The thesis mainly employs rational choice theory along with supplementary qualitative research methods in order to analyze the EU policies of the Turkish political parties. It finds out that the EU approaches of the political parties in Turkey differ in certain periods. Once it infers that those parties do not conduct consistent EU policies, it explains the changes in EU stances of the parties with their cost-benefit analyses. In the light of the findings of the research on the EU policies of the parties, the thesis concludes that electoral behavior, intraparty dynamics and party identity are the most significant variables which affect the interest perceptions of the parties. In other words, they are the main factors determining the EU stances of the parties.
Keywords: Avrupa Birliği_Türkiye; Siyasi Partiler